ANALISIS FILM NANTI KITA CERITA TENTANG HARI INI - Asti Haningtyas, S.I.Kom, M.I.Kom, Asti Haningtyas, S.I.Kom, M.I.Kom (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2022)
The film industry is booming right now, especially in Indonesia. As a means of entertainment and conveying messages to the public, various cinema themes have been produced. This study aims to qualitatively analyze the content (content analysis) in the exposure of the film "Nanti Kita Stories About Hari (NKCTHI)" which is a family drama genre that describes the position and role of a man, husband, and father in a family that is sued by a child. their children according to the development of the times. The message of NKCTHI's film is to challenge male domination as partner and father in a patriarchal culture where men still have the authority and center of power.